RADIATION THERAPY AND HEARING LOSS - Bhandare, Niranjan (2010)
A review of literature on the development of sensorineural hearing loss after high-dose radiation therapy for head-and-neck tumors and stereotactic radiosurgery or fractionated stereotactic radiotherapy for the treatment of vestibular schwannoma is presented. Because of the small volume of the cochlea a dose–volume analysis is not feasible. Instead, the current literature on the effect of the mean dose received by the cochlea and other treatment- and patient-related factors on outcome are evaluated. Based on the data, a specific threshold dose to cochlea for sensorineural hearing loss cannot be determined; therefore, dose–prescription limits are suggested. A standard for evaluating radiation therapy–associated ototoxicity as well as a detailed approach for scoring toxicity is presented.